Intrapulmonary mature Teratoma - Krishnamurthy S; Saini Monika; Kumar Rekha V (BMC, 2006)
Abstract Teratomas are tumors consisting of tissues derived from more than one germ cell line. Criteria for pulmonary origin are exclusion of a gonadal or other extra-gonadal primary site and origin entirely within the lung. Lung teratomas are rare, and for unknown reasons commonly involve the upper lobe of the left lung. We report a case of intrapulmonary teratoma in a 38-year-old male and review the relevant literature.